2017
DOI: 10.1016/j.ausmj.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Double Jeopardy – 50 Years On. Reviving a Forgotten Tool that Still Predicts Brand Loyalty

Abstract: Scientific knowledge builds by continuously subjecting its known laws to differentiated replications. Empirical generalisations capturing the Law of Double Jeopardy have been extensively tested in this way for decades, and rightly so because they continue to provide a valuable managerial key to the multi-million dollar question of how brands grow. This research continues that work, first by extending knowledge of the operation of Double Jeopardy in the less familiar conditions of long-run continuous buying, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 36 publications
4
42
0
Order By: Relevance
“…For almost 60 years, the pattern consistently shows that small brands have fewer buyers, who purchase slightly less frequently, and bigger brands have more buyers who buy slightly more frequently (Ehrenberg & Goodhardt, 2002;Sharp et al, 2012). The difference between big brands and small brands is the percentage of category buyers purchasing in the period, and not their loyalty (often measured as purchase frequency, or share of category) (Graham et al, 2017;Greenacre et al, 2015;Uncles & Kwok, 2009). The pattern occurs in FMCGs including instant coffee (Greenacre et al, 2015), toothpaste, carbonated soft drinks, yogurt, instant noodle, soy sauce (Uncles & Kwok, 2009), and many other categories such as washing detergent (Scriven et al, 2017).…”
Section: Dj-a Behavioral Loyalty Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…For almost 60 years, the pattern consistently shows that small brands have fewer buyers, who purchase slightly less frequently, and bigger brands have more buyers who buy slightly more frequently (Ehrenberg & Goodhardt, 2002;Sharp et al, 2012). The difference between big brands and small brands is the percentage of category buyers purchasing in the period, and not their loyalty (often measured as purchase frequency, or share of category) (Graham et al, 2017;Greenacre et al, 2015;Uncles & Kwok, 2009). The pattern occurs in FMCGs including instant coffee (Greenacre et al, 2015), toothpaste, carbonated soft drinks, yogurt, instant noodle, soy sauce (Uncles & Kwok, 2009), and many other categories such as washing detergent (Scriven et al, 2017).…”
Section: Dj-a Behavioral Loyalty Patternmentioning
confidence: 99%
“…For several decades, marketing researchers became accustomed to working with consumer purchase data in fast moving consumer goods (FMCGs), developing approaches to guide their analyses (Graham et al, 2017). When documenting brand loyalty relative to size, use double jeopardy (DJ) (Ehrenberg et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Allenby and Lenk, 1995; Bartels and van den Berg, 2011). The second reason for interest in NM is its relation to the well-known Double Jeopardy effect (Graham et al, 2017). Double Jeopardy is a pattern by which small brands obtain somewhat less loyalty, whereas large brands obtain somewhat higher loyalty from their buyers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…but gives no evidence of loyalty at the BOP or any other level. However, it has been repeatedly shown that most brand buyers in any customer base are predictably light buyers (Graham et al, 2017).…”
Section: Extending the Analysis To A New Contextmentioning
confidence: 99%